Work-relatedness Assessment of Hexavalent Chromium-induced Occupational Lung Cancer: A Review and Case Investigation - Phongam , Parit; Brohmwitak , Charubongse (Biomedical Sciences and Clinical Medicine, 2022)
Stainless steel has long been ubiquitously used in cookware manufacturing. In the production process, workers are potentially subject to exposure to many metal fumes, including chromium. Lung cancer is not uncommon in Thailand; however, lung cancer caused by hexavalent chromium [Cr (VI)] exposure had never previously been reported. A worker presented with respiratory symptoms and weight loss for 3 months. After rigorous investigation, the diagnosis was a non-small cell cancer (adenocarcinoma). He had worked at stainless steel polishing for 25 years without any history of smoking or other health risk factors. Polishing chromium-containing metal and lubricating it with trivalent chromium [Cr (III)] wax can create heat high enough to produce the known human lung carcinogen Cr (VI). Instead of wearing an appropriate respirator, he usually wore an activated charcoal mask. During his health treatment, an occupational medicine physician was consulted regarding the work-relatedness of his cancer. This article reviews the process of work-relatedness assessment of non-small cell lung cancer in Cr (VI) exposure by workers in the stainless steel industry and provides details of the first case of what from an occupational medicine point of view the authors consider an occupational disease.